2006
DOI: 10.1002/nag.471
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of test data for selection of 3-D failure criterion for sand

Abstract: SUMMARYData from three-dimensional experiments performed on sand in true triaxial equipment have been reviewed to sort out apparent disarray resulting from their interpretation. This has been done based on analyses made possible by recent developments and understanding of factors influencing sand behaviour: occurrence of shear banding, boundary conditions and/or specimen slenderness ratio, cross-anisotropy, and stability of experimental technique. These factors are reviewed and test data from the literature ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 43 publications
4
29
0
3
Order By: Relevance
“…Several experimental studies have shown that the friction angle in TE, e CS  , is close to c CS  for pluviated sands (e.g. Vaid et al 1990;Lade 2006). In the present study, a stress ratio Fig.…”
Section: Fig 10 Critical State Strength Of Hostun Sand In Compressisupporting
confidence: 71%
“…Several experimental studies have shown that the friction angle in TE, e CS  , is close to c CS  for pluviated sands (e.g. Vaid et al 1990;Lade 2006). In the present study, a stress ratio Fig.…”
Section: Fig 10 Critical State Strength Of Hostun Sand In Compressisupporting
confidence: 71%
“…Usually, the 2D strength criterion underestimates the actual strength when b ½ 5 ðs 0 2 2 s 0 3 Þ=ðs 0 1cyc 2 s 0 3 Þ . 0, where b represents the role of intermediate stress (Matsuoka and Nakai 1982;Lade 2006). However, in this study, the 2D failure criterion still can predict the shear strength with acceptable accuracy for small b values (≅ 0.01).…”
Section: Finite-element Simulationmentioning
confidence: 64%
“…These conflicting observations may be caused by the differences in sample conditions or testing methods. The data of three-dimensional true triaxial experiments from the literature were evaluated and factors influencing the angle of shearing resistance were reviewed by Lade et al [9]. It is well accepted that different mechanical behaviors may arise from samples with similar void ratios but different fabrics.…”
Section: Introductionmentioning
confidence: 99%